2011
DOI: 10.3945/ajcn.110.003350
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract stone occurrence in the Women’s Health Initiative (WHI) randomized clinical trial of calcium and vitamin D supplements

Abstract: Daily supplementation with CaD for 7 y was associated with an increase in the number of self-reported urinary tract stones. These findings have implications for CaD supplement use. This trial was registered with the WHI at clinicaltrials.gov as NCT00000611.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(77 citation statements)
references
References 36 publications
1
72
0
4
Order By: Relevance
“…In women receiving 1 g calcium plus 10 µg vitamin D daily for a mean of seven years, a higher incidence of self-reported urinary tract stones was reported compared to those receiving placebo (Wallace et al, 2011). Plasma or serum 25(OH)D concentrations were not measured in this study.…”
Section: Vitamin D Intake or Status And Long-term Health Outcomes In mentioning
confidence: 52%
“…In women receiving 1 g calcium plus 10 µg vitamin D daily for a mean of seven years, a higher incidence of self-reported urinary tract stones was reported compared to those receiving placebo (Wallace et al, 2011). Plasma or serum 25(OH)D concentrations were not measured in this study.…”
Section: Vitamin D Intake or Status And Long-term Health Outcomes In mentioning
confidence: 52%
“…Because of the known risk of kidney stones with calcium supplement intake above 1500 mg [1,4,5] and emerging concerns that calcium supplementation is associated with increased risk of myocardial infarction [12], excessive calcium intake is also a potential quality and safety concern.…”
Section: Discussionmentioning
confidence: 99%
“…(2) In addition to mild and often self-limited gastrointestinal intolerance, the most important confirmed side effect of supplementation is a 17% increase in nephrolithiasis. (3) The calcium supplement landscape, however, has changed considerably since the publication of two meta-analyses by Bolland and colleagues in 2010 (4) and 2011, (5) concluding that calcium supplements increase the risk of both coronary and cerebrovascular events. The first meta-analysis pooled 15 placebo-controlled trials of calcium supplements without vitamin D and found a statistically significant 31% increased risk of myocardial infarction (p ¼ 0.04) and a nonsignificant 20% increased risk of stroke (p ¼ 0.11) among calcium-treated individuals.…”
mentioning
confidence: 99%